MANAJEMEN KOMUNIKASI PEMBERDAYAAN MASYARAKAT MELALUI PNPM - Achmad Jamil; Suleman Nur Alam (Akademika, 2015)
Low levels of health and education in poor households is a major challenge that must be facedby Indonesia. Community empowerment is a process of preparing the community through avariety of resources, opportunities, knowledge, and expertise to increase the capacity indetermining their future, as well as participate in and influence the life of the community itself(Ife in Martono, 2011). Diaz Bordinave (Melkote and Steeves, 2006) noted that in thisapproach, participation is often expected to live by the source and change agents (people whopay attention to people who have not received empowerment). In a participatory approachfrom below (bottom up) the public be persuaded to take part in independent activities, butlocal settlement fundamental issues selected by an agent of change. One of the communityempowerment program is the National Program for Community Empowerment in Rural Areas(PNPM MPd) Healthy Generation Intelligent initiated by the government since 2007. Theresults show managerial ability for the credibility of the participants and the facilitatorperspective in the perspective of the perpetrators affect the success of implementation ofPNPM program MPd healthy generation intelligent Ciranjang implemented in the district,Cianjur.